TREE AS PASSIVE COOLING, AN ALTERNATIVE APPROACH TO ENHANCE THE THERMAL COMFORT IN BUILDING IN SOUTHEAST SULAWESI, A TROPICAL REGION - Aditya Rachman (Dinamika : Jurnal Ilmiah Teknik Mesin, 2014)
Reducing the role of the conventional cooling machines into the building to make the thermal comfort is so imperative as their massive energy consumption and their contribution to the global climate change. Shifting into less energy consumed cooling methods using the locally available vegetative sources as passive cooling, can be one of the appropriate methods. The aim of this study is to investigate the influence of trees to the thermal comfort performance in a building in Southeast Sulawesi, a region, geographically, located in the equator line with its high daily solar radiation intensity. It conducts an experiment on a small scale building with various tree configurations. The result shows that the trees provide the effect of lowering temperature and maintaining the relative humidity of air, contributing into making the thermal comfort-ability in the building. A comprehensive discussion, using the Psychometric chart, regarding to the reason for the phenomenon is also presented in this paper.